EdD Student Research for Scholarly Practice - Sherisse G. Jackson; Yuechen Sun (Impacting Education, 2022)
This article introduces one design concept of the Carnegie Project on the Education Doctorate’s (2022) framework, which is the emphasis on students becoming scholarly practitioners. In addition, this article provides an overview of each article appearing in this issue.